Four thoughts on place and The Jungle. (1st November 2019) - Lamont Bishop, Olivia
AbstractThe Jungle (2018), by Joe Murphy and Joe Robertson, is a play that focuses on the experiences of the residents and volunteers of the refugee camp known as the Calais Jungle, where London audiences experienced a recreation of this camp in a West End theatre. This intervention discusses the ethics surrounding the theatrical recreation of such places which are associated with conflict and displacement. Considering the positionality of the audience and the creators of the play, as well as analysing its institutional framing, this piece examines the issues inherent within recreating places at a distance.